Dust extinction towards the type Ia supernova 2012cu in NGC 4772. (April 2020) - Gao, Weijia; Zhao, Ruining; Gao, Jian; Jiang, Biwei; Li, Jun
Abstract: Using photometric and spectroscopic data of Supernova (SN) 2012cu, a fairly reddened type Ia supernova, we derived its color excess curves and probed the dust extinction in its host galaxy, NGC 4772. In order to derive the extinction as a function of wavelength (i.e., A λ ), we model the color excess curves of SN 2012cu in terms of dust models consisting of silicate and carbonaceous (graphite or amorphous carbon) dust. The modeled extinction law towards SN 2012cu extends flatly to the far-ultraviolet (UV) bands, which is much flatter than those of the Milky Way and Magellanic Clouds, and the 2175 Å feature is very weak or absent. The flatness of the modeled extinction curve in the UV bands suggests a "grey" extinction law of the active galactic nucleus in the vicinity of the SN 2012cu-Earth line of sight. Our results indicate that the sizes of the dust in the ISM towards SN 2012cu in NGC 4772 are larger than those of the Milky Way and the Large Magellanic Cloud, and much larger than that of the Small Magellanic Cloud. The best fitting gives an observed visual extinction towards SN 2012cu of A V ≈ 2.6 mag, a reddening of E ( B − V ) ≈ 1.0 mag, with a total-to-selective extinction ratio R V ≈ 2.7, consistent with previous results. Highlights: The novel study to adopt an improved physical two-component dust model to derive the extinction laws towards SN 2012cu. The novel study to use the combination of photometric and spectroscopic data of SN 2012cu for fitting. The fitting results of the modeled extinction curves suggest a "grey" extinction law in the host AGN galaxy of NGC 4772. The modeled results indicate that size distribution of dust in NGC 4772 is skewed to large grains.